Hierarquização de atributos ao empreendedorismo em Três Lagoas - MS - Ribeiro, Silvio Paula (Universidade do Vale do Rio dos Sinos, 2019)
This research aimed to establish the hierarchy of attributes to guide new developments in the city of Três Lagoas (Mato Grosso do Sul state). To this end, categories and subcategories of attributes were identified and described, and twenty experts (teachers, researchers and professionals from industry development organizations) were consulted about the influence of the attributes of entrepreneurship in the activity in the municipality. The hierarchy of attributes was then measured based on the evaluation of 165 (one hundred and sixty-five) undergraduate students of Business Administration, Accounting and Production Engineering courses of a public Federal Institutions of Higher Education (IFES) and a private Higher Education Institutions (IES) considered as potential entrepreneurs. For the data analysis, the Analytic Hierarchy Process (AHP) methodology was applied. The results revealed the supremacy of the material attributes in relation to the social and cultural attributes as priority to the establishment of new enterprises in the city of Três Lagoas (Mato Grosso do Sul state). In other words, the potential entrepreneurs attach greater value to formal resources (laws, rules and norms) for local entrepreneurship. In relation to the subcategories, the final priorities indicated in the order: market opening; policies / government; own networks; support services; attitudes; physical infrastructure; universities; mentors and negotiators; cultural values; talented workers; stories of entrepreneurs; investment capital and customs.
Keywords: Empreendedorismo; Teoria institucional; Recursos; Atributos; Análise Multicritério; Entrepreneurship; Institutional theory; Resources; Attributes; Multi-Criteria Analysis; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis